1992
DOI: 10.1136/adc.67.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Failure to prevent nicotine addition in young people with diabetes.

Abstract: The habit of smoking is usually acquired at a young age and it is particularly undesirable in individuals with diabetes. A study was carried out to assess objectively the prevalence of smoking in young patients with diabetes and whether younger age at onset of diabetes (implying exposure to health education) reduced the incidence of smoking. Ninety nine young adults with diabetes attending the routine clinic were studied using a structured interview and assay of a urinary nicotine metabolite (cotinine (HbAI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 9 publications
1
31
0
Order By: Relevance
“…The latter study also reported higher rates of illicit drug use and risky sexual behavior in young persons with diabetes. Also, anti-smoking efforts have little effect in young persons with type 1 or type 2 diabetes (Ardron et al, 1988;Ismail et al, 2000;Masson et al, 1992). A survey study also revealed that 68% of young persons with type 1 diabetes habitually use street drugs more than once a month, and 72% of them are unaware of the adverse effects of drug use on diabetes (Ng et al, 2004).…”
Section: Problem Of Tobacco Use In Persons With Diabetesmentioning
confidence: 94%
“…The latter study also reported higher rates of illicit drug use and risky sexual behavior in young persons with diabetes. Also, anti-smoking efforts have little effect in young persons with type 1 or type 2 diabetes (Ardron et al, 1988;Ismail et al, 2000;Masson et al, 1992). A survey study also revealed that 68% of young persons with type 1 diabetes habitually use street drugs more than once a month, and 72% of them are unaware of the adverse effects of drug use on diabetes (Ng et al, 2004).…”
Section: Problem Of Tobacco Use In Persons With Diabetesmentioning
confidence: 94%
“…The age-adjusted prevalence of smoking is similar for people with or without diabetes [89,90]. This is a big problem in teenagers with diabetes, and is challenging to approach [91,92]. Even passive smoking may increase the risk of cardiovascular disease [93].…”
Section: Atherosclerosis Is Earlier and More Severe In Type 1 Diabetesmentioning
confidence: 95%
“…98 Similarly low smoking-prevalence rates of 9% were reported among 11-to 18-year-olds with diabetes, 99 but unlike other studies, this sample did not include young adults. In another study that included objective measures of active smoking among diabetic patients aged 15 to 31 years, Masson et al 100 found that although 31% of the patients admitted to smoking on a questionnaire delivered by a nurse in the patient's clinic setting, urinary cotinine (nicotine metabolite) assays suggested that up to 48% were actively smoking. Fourteen percent of the sample were past smokers.…”
Section: Illness-and Treatment-related Complicationsmentioning
confidence: 96%